Roland Humphrey is wearing a what? - Kiernan-Johnson, Eileen; Revenaugh, Katrina (Boulder, Colorado Huntley Rahara Press, 2012)
Roland Humphrey is a little boy who likes sparkly things and bright colors. He likes both sports and ballet, and doesn't understand why girls can like both but not boys. Will he bow to peer pressure, or follow his heart and be the authentic Roland Humphrey?
Keywords: Gender identity -- Juvenile fiction; Sex role -- Juvenile fiction; Clothing and dress -- Juvenile fiction; Individuality -- Juvenile fiction; Conformity -- Juvenile fiction; Picture books for children